Exploring coping mechanisms among traumatic brain injury survivors: a phenomenological study - Abdul Rashid, Nor'ain; Khuan, Lee; Baharom, Anisah; Arshad, Mohd Mursyid (ASEAN Neurological Association, 2025)
Objective: The goal of this study was to investigate and comprehend the coping strategies used by traumatic brain injury (TBI) survivors to adjust to the changes that occur after the injury in an Asian rehabilitation set up. Methods: The study used a qualitative phenomenological design. Twenty participants, including TBI survivors and their family members, were recruited using purposive sampling. In-depth semi-structured interviews were used to gather data, and thematic analysis was used for analysis. Results: Twenty participants were interviewed, 16 were TBI survivors, 6 were relatives of the survivors. Two primary themes emerged: emotion-focused coping (e.g., seeking social support, religious practices) and problem-focused coping (e.g., physical aids, behavioural modifications). The individuals’ reactions to the changes and difficulties they faced were reflected in these coping mechanisms. Conclusion: The integration of religious and spiritual coping strategies in the rehabilitation phase is particularly important in a cohort of Asian TBI survivors